Phase angle is associated with the length of ICU stay in patients with non-ST elevation acute coronary syndrome - Polegato, Bertha Furlan [UNESP]; Herrera, Monique Aguilar [UNESP]; Pereira, Bruna Letícia Buzati [UNESP]; Silva, Renata Aparecida Candido [UNESP]; Gonçalves, Andrea Freitas [UNESP]; Cavallari, Karelin Alvisi [UNESP]; Costa, Nara Aline [UNESP]; Tanni, Suzana Erico [UNESP]; Azevedo, Paula Schmidt [UNESP]; Dorna, Mariana Souza [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP]; de Paiva, Sergio Alberto Rupp [UNESP]; et al. (Springer Nature, 2017)
Background: The aim of this study was to evaluate the associations between phase angle (PhA), sarcopenia, and the length of stay (LOS) in the coronary intensive care unit (ICU) in patients with non-ST acute coronary syndrome (NSTE-ACS). Methods: This was a prospective observational study that evaluated 80 patients with NSTE-ACS over the age of 18 years, admitted to the ICU from January to June 2014. Upon admission, the patients’ demographic information was recorded. Handgrip strength and bioelectrical impedance analysis (BIA) were performed, and blood samples were taken within the first 72 h of admission. All of the patients were followed during their ICU stays. Results: We evaluated 80 patients, five were excluded due to impossibility of assessing handgrip strength, and seven patients were not subjected to BIA. Thus, 68 patients with a mean age of 63.3 ± 13.1 years were included in the analysis. Among these patients, 60.1% were male, 27.9% of the patients had sarcopenia, 8.8% had LOSs ≥8 days, and median phase angle was 6.5 (6.1–7.3)°. Multiple logistic regression adjusted for age and gender revealed that PhA was not associated with the presence of sarcopenia. Additionally, PhA (OR 0.337; CI 95% 0.118–0.961; p = 0.04) but not sarcopenia (OR 0.517; CI 95% 0.055–4.879; p = 0.56) was associated with an increased LOS. Conclusions: PhA is associated with LOS in patients with NSTE-ACS. Additionally, there was no association between PhA and sarcopenia.
Keywords: Acute coronary syndromes; Bioelectrical impedance; Phase angle; Sarcopenia; Vitamin D